INCREASE IN LITERACY USING LITERACY BOX IN SMP NEGERI 1 MANDE - Sulistia, Dea Tri (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Literacy is believed to be capable of improving student education quality. One of the important things that requires improvement at the school level is the culture of literacy. The world places a high value on having the ability to read and write. The goal of this study was to ascertain how the literacy program was being implemented at SMP Negeri 1 Mande. This study is a two-cycle classroom action research project. Students write a word in the first cycle and then place it in the literacy box. Students use the same media in the second cycle to organize a series of words into a poetry sentence that puts greater attention on indicators whose improvement has not been optimal. The subjects in this study were eighth-grade students. The method of implementing the activities used is qualitative-descriptive. Observation and documentation are used for data processing and analysis. The study was conducted for three months, starting from the beginning of the deployment on March 23 and ending on June 28, 2022. The results of research at SMP Negeri 1 Mande show that the literacy movement carried out by researchers is able to change the culture of literacy in students. Implementation of this literacy activity requires support from various stakeholders, including teachers and school leaders.